STRATEGI PEMBELAJARAN AGAMA ANAK MELALUI PENDIDIKAN MULTIKULTURAL DI PAUD CLARISTA KUDUS TAHUN 2013/2014 - Husnita, Laila (BELIA: Early Childhood Education Papers, 2014)
Learning process is closely related to interaction among the teacher, the students, and the source of the learning itself. The source of learning is frequently used by the teacher to support the learning activity. Introduction of basic mathematics concept should be given from an early age. One of the way to develop basic mathematics to children is by learning process at school. Learning process which is held in communities is the effective way to introduce basic mathematics concept. According to Sudjana and Rivai (Prastowo, 2012:2), source of learning is the energy that can be used to give simplicity to someone in his or her learning.The aim of this research is to know the usage of cardboard waste as the learning source in developing basic concept of mathematics. This research is kind of an experiment pretest-posttest control group design. The sampling process uses simple random sampling technic, as the samples are Taman Indria kindergarten as the experiment group and PGRI 02 Mlatiharjo 1 kindergarten as the control group.The t paired test between pretest and posttest in experiment group has obtained significant score (2-tailed) < 0,05 is that 0,000 that means there is a significant difference , however the t paired test between pretest and posttest in control group has obtained significant score (2-tailed) < 0,05 is that 0,018 that means there is no significant enhancement. The result test of t paired posttest in control and experiment group is that there are significant difference because it has significant score (2-tailed) < 0,05 is that 0,000 that means there is significant difference There is a distinction in basic concept of mathematics in children of experiment group before and after they are given the cardboard waste as the learning source. It is known that there is a difference comprehension of basic concept of mathematics between the children of experiment and control group after the treatment. Therefore, cardboard waste as the learning source is effective to develop basic concept of mathematics in 5-6 years old children.chool as the education facilities should give another learning source or another literature to develop the basic concept of mathematics in order to children can get better basic concept of mathematics and they will have good understanding in it.Many early childhood education institution that accepts a wide range of diversity, both differences in ethnicity, race, culture, and religion. But in fact the field, which is not too much attention to early childhood diversity that exists, especially in terms of multireligious. Many educators or teachers in learning, teaching leveler way to develop children's moral and religious. Clarista Kudus early childhood is one of the non-formal schools have multicultural school environment. In the process of learning, it have specific strategies and programs developed to teach moral values and religion of the child who has a multireligious within the scope of multicultural education. The purpose of the reseach describe the moral values and religion are taught, applied the concept of multicultural education, moral and religious learning strategies children through multicultural education in Clarista early childhood and constraints. This reseach used a qualitative case studies approach. Researchers used a observation method, interview, and documentation in collecting the data. Then to analyze the data in this reseach researchers used reduction data, display data, conclusion and verification. From the research, the researchers found that the moral values and religion in early childhood applied in there is basic faith, worship, love to Almighty God and loving God's creatures and tolerance, mutual respect, empathy, forgiveness, honesty, discipline, responsibility, self-contained. The concept of multicultural education is applied is organizing a national based education through habituation and play of process interaction while learning creative by teaching children about the beauty of the difference for child to respect and loving differences or multicultural that exist in the surrounding environment that early enrollment nationally, accept children and multicultural environment (religious, ethnic, and cultural), provide religion learning facilities in accordance beliefs or the religious that are believed to child , and held a celebration of religious. Religious learning strategy used is the classical approach to learning according to the religion class each child through habituation and training strategies, learning strategies, strategies playing, exemplary strategies with learning methods lecture, question and answer, exemplary, sociodramas, as well as the method of travel works. These strategies are poured into all aspects of learning activities.There are two obstacles in the implementation of the strategy, the internal resistance of the attitude of children who are still unstable, easily bored, and external barriers that inadequate media and school management in terms of making plan learning activities that are less good.